Respuesta :

Answer:

(a/3

[tex]( \frac{a}{3} - \frac{b}{5} ) {}^{2} [/tex]

[tex] \frac{ {a}^{2} }{9} - \frac{2ab}{15} + \frac{b {}^{2} }{25} [/tex]

Answer:

Step-by-step explanation:

(x + y +z)^2 = x² + y² + z² + 2xy + 2yz + 2zx

x = a/3

y = -b/6

c = -1

[tex][\frac{a}{3}-\frac{b}{6}-1]^{2}=(\frac{a}{3})^{2}+(\frac{-b}{6})^{2}+(-1)^{2}+2*\frac{a}{3}*\frac{-b}{6}+2*\frac{-b}{6}*(-1)+2*\frac{a}{3}*(-1)\\\\\\=\frac{a^{2}}{9}+\frac{b^{2}}{36}+1-\frac{ab}{9}+\frac{b}{3}-\frac{2a}{3}[/tex]

ACCESS MORE